Review of the genus Pseudodolbina Rothschild, 1894, with the description of a new species from Yunnan, China (Lepidoptera: Sphingidae) - Jiang, Zhuo-Heng; Yan, Ming; Wang, Jia-Xin; Hu, Shao-Ji (Zootaxa, 2024)
The two species currently included in the genus Pseudodolbina Rothschild, 1894, Pseudodolbina fo (Walker, 1856) and Pseudodolbina aequalis Rothschild & Jordan, 1903, were studied and a new species, Pseudodolbina yunnana sp. nov., was described from Yunnan, China. The diagnostic features and a distribution map of three species are provided, with a phylogenetic analysis based on DNA barcodes.